PENGARUH PEMBELAJARAN DARING TERHADAP MINAT BELAJAR PESERTA DIDIK KELAS VIII SMPN 7 SUNGAI RAYA - Malisa, Malisa; Asrori, Muhammad; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to determine the effect of online learning on the learning interests of Class VIII students in SMP Negeri 7 Sungai Raya. This study uses a quantitative approach with a form of correlational research. The number of samples in this study as many as 37 respondents from a total population of 136 learners Class VIII A to VIII E. Data collection techniques used are indirect communication techniques with data collection tools in the form of questionnaires distributed through google Forms.. The results of data analysis in the study showed that: (1) online learning students Class VIII SMP Negeri 7 Sungai Raya included in the high category with a percentage of 70%, (2) interest in learning students Class VIII SMP Negeri 7 Sungai Raya has a percentage of 64% classified as medium category, and (3) based on research online learning has an influence on the interest of learning students Class VIII SMP Negeri 7 Sungai Raya. This is in line with the calculation of simple linear regression, obtained the equation Y"™= 26.047 + 0.608 X. Significance value obtained by 0.000 0.05%. This means that H0 was rejected and Ha was accepted so that it was concluded that there was an influence of online learning on the learning interests of VIII grade students of SMP Negeri 7 Sungai Raya.